The Effect of Household Storage Tanks/ Vessels and User Practices on the Quality of Water: a systematic review of literature - Manga, Musa; Ngobi, Timothy G.; Okeny, Lawrence; Acheng, Pamela; Namakula, Hidaya; Kyaterekera, Elizabeth; Nansubuga, Irene; Kibwami, Nathan (Environmental Systems Research, 2021)
Household water storage remains a necessity in many communities worldwide, especially in the developing countries. Water storage often using tanks/vessels is envisaged to be a source of water contamination, along with related user practices. Several studies have investigated this phenomenon, albeit in isolation. This study aimed at developing a systematic review, focusing on the impacts of water storage tank/vessel features and user practices on water quality. Database searches for relevant peer-reviewed papers and grey literature were done. A systematic criterion was set for the selection of publications and after scrutinizing 1106 records, 24 were selected. These were further subjected to a quality appraisal, and data was extracted from them to complete the review.Microbiological and physicochemical parameters were the basis for measuring water quality in storage tanks or vessels. Water storage tank/vessel material and retention time had the highest effect on stored water quality along with age, colour, design, and location. Water storage tank/vessel cleaning and hygiene practices like tank/vessel covering were the user practices most investigated by researchers in the literature reviewed and they were seen to have an impact on stored water quality.There is evidence in the literature that storage tanks/vessels, and user practices affect water quality. Little is known about the optimal tank/vessel cleaning frequency to ensure safe drinking water quality. More research is required to conclusively determine the best matrix of tank/vessel features and user practices to ensure good water quality.
Keywords: Water quality, Water contamination, Water storage tank/vessel, Water storage tank/vessel features, Water users practices